Investigating mathematics teachers' acceptance of eBook - Abd Jalal, Azlin; Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani (IDOSI Publications, 2014)
The eBook, a low cost netbook complete with digital textbook softwares, were provided for each students, in line with the concept of 1 student: 1 laptop. This study focuses on assessing the acceptance of eBook among mathematics teachers in the teaching and learning and also examining the relationships among the factors namely are perceived usefulness, perceived ease of use, attitude towards eBook and behavioural intention. Data were collected from 304 mathematics teachers in selected primary schools in Terengganu using a survey questionnaire. The finding indicates that the levels of all four constructs are moderate. Results also showed that perceived usefulness, perceived ease of use, attitude and behavioural intention have strong positive significant inter correlations. This implied that mathematics teachers should be updated on trainings on the eBook usage, with the right applications and softwares for mathematics teaching, increasing the ease of using it, thus the positive attitudes and increasing the intention in using eBook in mathematics teaching and learning.